2006
DOI: 10.1097/01.hp.0000194203.58594.66
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ocular Aberrations on Retinal Laser Damage Thresholds in the Human Eye

Abstract: For the dark-adapted human eye the diffraction limited retinal image is approximately 2.8 microm in diameter for green light, although the estimation of the size of the retinal image resulting from the incidence of a collimated beam on the cornea is problematical and has been estimated to be anywhere from 10 to 30 microm. The resolution of this difference is important for the accurate determination of the retinal hazards of optical sources and for setting safety limits for laser-retinal exposure. Using literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The human visual system is known to suffer from aberrations, diffraction, scatter, finite receptor size and noise in the neural pathways. The smaller pupil size may have some advantages in its superiority for image formation, such as an increasing depth of focus, a decrease in HOAs13 14 and a decrease in light scatter,15 all of which may, to some extent, offset the deleterious effects of reduced luminance16 and diffraction. Accordingly, the smaller pupil may moderate the impact of astigmatic defocus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human visual system is known to suffer from aberrations, diffraction, scatter, finite receptor size and noise in the neural pathways. The smaller pupil size may have some advantages in its superiority for image formation, such as an increasing depth of focus, a decrease in HOAs13 14 and a decrease in light scatter,15 all of which may, to some extent, offset the deleterious effects of reduced luminance16 and diffraction. Accordingly, the smaller pupil may moderate the impact of astigmatic defocus.…”
Section: Discussionmentioning
confidence: 99%
“…Strang et al 13 reported that the contrast sensitivity function with a larger pupil was better than that with a smaller pupil at some spatial frequencies, owing to the complex interactions between pupil size and defocusing. The optical modulation transfer function of the human eye has been reported to be equivalent to that of the perfect diffraction system-limited system at a pupil diameter of 1 mm but not of 1.5 or 2 mm 14 15 17 18. Although the exact reason still remains unclear, the authors assume that the pupil-dependent effect of increasing depth of focus, and a decrease in HOAs and light scatter, on UCVA may be larger than the counteractive effect of diffraction and reduced luminance for a 1 mm pupil, not in eyes with low astigmatism, but in eyes with high astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…The large-diameter beam "samples" more of the ocular aberrations and is expected to result in a more distorted retinal beam spot. 19 Effectively correcting for these aberrations should therefore have a more significant impact on the quality of focus of the larger diameter beam. The diffraction-limited spot size is 3 m for the 6-mm beam and 6 m for the 3-mm beam.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular aberrations will lead to a poorer focus of the large-diameter beam than of the smalldiameter beam. 19 Therefore, the large-diameter beam should exhibit a larger difference between the ED 50 measured with and without wavefront correction.…”
Section: Introductionmentioning
confidence: 99%
“…Corneal structures can be disrupted, reaching form photokeratitis until perforation [8,29,30]. The extent of intraocular damage however, is dependent on pupil size [31]. Vitreous [32], subretinal [33] or chorioretinal hemorrhages [32], as well as retinal edema or scars can also occur [34], and hypopigmentation [35], pigment clumps [36] and choroidal neovascularization [37] can develop.…”
Section: Laser-induced Eye Injuries -Morphologic Findings and Therapymentioning
confidence: 99%